2016
DOI: 10.1103/physrevb.94.214104
|View full text |Cite
|
Sign up to set email alerts
|

Phase field simulations of plastic strain-induced phase transformations under high pressure and large shear

Abstract: Pressure and shear strain-induced phase transformations (PTs) in a nanograined bicrystal at the evolving dislocations pile-up have been studied utilizing phase field approach (PFA).The complete system of PFA equations for coupled martensitic PT, dislocation evolution, and mechanics at large strains is presented and solved using finite element method (FEM). The nucleation pressure for high pressure phase (HPP) under hydrostatic condition near single dislocation was determined to be 15.9 GPa. Under shear, a disl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 119 publications
(233 reference statements)
5
69
0
1
Order By: Relevance
“…The external pressure can be even smaller than the equilibirum pressure. Such a mechanism has been confirmed more quantitatively utilizing an analytical model of nucleation at the dislocation pile up in [11,12] and phase field simulations of strain-induced transformations in a bi-crystal in [13,14]. The G to D transition occurs without barrier as shear increases but nuclei cannot grow significantly because the stresses decrease with distance away from the defect tip.…”
Section: Fig 4: the Xps Spectra Of Carbon Of The Sample Before (Bottmentioning
confidence: 90%
“…The external pressure can be even smaller than the equilibirum pressure. Such a mechanism has been confirmed more quantitatively utilizing an analytical model of nucleation at the dislocation pile up in [11,12] and phase field simulations of strain-induced transformations in a bi-crystal in [13,14]. The G to D transition occurs without barrier as shear increases but nuclei cannot grow significantly because the stresses decrease with distance away from the defect tip.…”
Section: Fig 4: the Xps Spectra Of Carbon Of The Sample Before (Bottmentioning
confidence: 90%
“…It was suggested that the large fraction of these lattice defects and their interactions (especially interaction between the dislocations and grain boundaries) lead to enhanced localized pressure which finally results in the formation of high‐pressure phases under lower pressures . Recent theoretical studies by phase field approach and finite elements method confirmed that a dislocation pile‐up under shearing creates strong stress concentration and significantly increases the local thermodynamic driving force for pressure‐induced phase transformation at significantly low pressures . It should be noted that the reduction of pressure by shearing was also reported in some other phase transformations such as α ‐ ω transition in Zr and hexagonal‐wurtzite transition in BN …”
Section: Recent Findings On Hpt Processing Of Oxidesmentioning
confidence: 93%
“…The developed PFA was implemented in a finite element method (FEM) code COMSOL and was utilized for the first study of nucleation and growth of the HPP under normal stress and shear strain ( Fig. 3) 31,39,41,42) in a bicrystal. The obtained results prove that the superimposed plastic shear can reduce PT pressure by a factor of 10 and more.…”
Section: Phase Nucleation At Dislocation Pileupsmentioning
confidence: 99%